2009
DOI: 10.1002/fuce.200900062
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly (2,2′‐(1,4‐phenylene) 5,5′‐bibenzimidazole) (para‐PBI) and Phosphoric Acid Doped Membrane for Fuel Cells

Abstract: A detailed investigation of the polymerisation conditions for poly(2,2′‐(1,4‐phenylene)5,5′‐bibenzimidazole) (para‐PBI) in polyphosphoric acid (PPA) led to the preparation of high molecular weight polymer. The polymer solutions could be used directly to produce phosphoric acid (PA)‐doped PBI membranes by the PPA process. These membranes showed very high PA doping levels, i.e., up to ∼30 moles of PA per mole of PBI repeat unit. The ionic conductivity of the membranes was 0.24 S cm–1 at 160 °C. Fuel cell perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 20 publications
3
49
0
1
Order By: Relevance
“…Although the membrane must have a limit of operating temperature due to material safety, it is clear that high operating temperature allows for a higher voltage output under the same other conditions. Experimental tests conducted by Yu et al [50] reported similar results on the effect of fuel cell temperatures on the voltagecurrent performance [51] as shown in Fig. 8b.…”
Section: Validation To the Mathematical Modelmentioning
confidence: 52%
See 4 more Smart Citations
“…Although the membrane must have a limit of operating temperature due to material safety, it is clear that high operating temperature allows for a higher voltage output under the same other conditions. Experimental tests conducted by Yu et al [50] reported similar results on the effect of fuel cell temperatures on the voltagecurrent performance [51] as shown in Fig. 8b.…”
Section: Validation To the Mathematical Modelmentioning
confidence: 52%
“…The width of the current collection ribs is 1.0 mm. Figure 5 shows the simulated results in comparison with experimental results reported by Yu et al [50]. The results in Fig.…”
Section: Validation To the Mathematical Modelmentioning
confidence: 76%
See 3 more Smart Citations